Mincle-dependent Th17 adjuvanticity requires TNFR1 signaling in myeloid cells - Blamberg, Robert; Haberkamp, Carl; Pedersen, Gabriel Kristian; Rosenkrands, Ida; Schleicher, Ulrike; Schraml, Barbara U.; Yamasaki, Sho; Lang, Roland (Frontiers in Immunology, 2026)
Successful induction of protective T cells by recombinant protein vaccines requires adjuvants. The liposomal adjuvant system CAF01 induces robust Th17 responses in mice. CAF01 contains the synthetic glycolipid trehalose-6,6-dibehenate (TDB), whose recognition by the C-type lectin receptor Mincle is required for Th17 induction. In previous work, we identified a pivotal role of TNF in upregulation of Mincle expression in macrophages and Th17 adjuvanticity of CAF01. The question has remained on which cell type(s) TNF acts to mediate the Th17 adjuvanticity of CAF01, and whether TNF-induced Mincle upregulation is causative. We used conditional TNFR1-deficient mice to dissect cell type-specific contributions of TNF signaling in myeloid cells, DC and T cells to Th17 induction by the recombinant tuberculosis fusion protein H1 adjuvanted with CAF01. LysM-Cre-mediated deletion of TNFR1 on myeloid cells completely abrogated vaccine-induced Th17 differentiation, replicating the phenotype in mice deficient in TNF or treated with the TNF blocker Etanercept. In contrast, TNFR1 deletion in DC by Clec9a-Cre did not affect Th17 induction, and by CD11c-Cre only partially reduced Th17 cells. T cell-specific deletion of TNFR1 by Lck-Cre had no impact on Th17 differentiation after vaccination. TNFR1 was expressed highly, and deleted efficiently via LysM-Cre, in monocytes and in neutrophils. We recently showed that neutrophils are not required for the adjuvant effect of CAF01, but monocytes are essential. Therefore, we analyzed activation of monocytes by TDB and observed robust upregulation of Mincle expression and of the Th17-inducing cytokines IL-1β and IL-6, that was inhibited by Etanercept. Finally, we asked whether Th17 induction by TNF is causally linked to Mincle upregulation. Constitutive, TNF-independent transgenic Mincle expression partially restored Th17 induction by CAF01 despite TNF blockade. Thus, upregulation of Mincle by TNF plays a causal role, likely by enabling production of Th17-polarizing cytokines by myeloid cells upon enhanced sensing of the adjuvant component TDB.